Through My Eyes : The Autobiography of Ruby Bridges. - Bridges, Ruby. (New York : Scholastic Press, 1999)
Ruby Bridges recounts the story of her involvement, as a six-year-old, in the integration of her school in New Orleans in 1960.
Keywords: Bridges, Ruby -- Juvenile literature; Bridges, Ruby; Afro-American children -- Biography -- Louisiana; Afro-Americans -- Biography -- Louisiana; School integration -- Juvenile literature. -- Louisiana; Afro-Americans -- Biography; School integration -- Louisiana; New Orleans (La.) -- Race relations; New Orleans (La.) -- Race relations